Evaluation of food habits and information levels of elite table tennis players and trainers - Cimen, O.; Kaza, M.; Taskin, C. (Turkish Journal of Sport and Exercise, 2014)
The aim of the study was to assess food habits and information levels of elite table tennis players and trainers. The universe of the study involves table tennis sportsmen and trainers; its sample involves 94 sportsmen and 44 trainers randomly chosen from the universe as well. The research is of a screening model directed to the situation determination. The data collection tool used in this research consists of 3 sections. In the first section, a personal information form was developed to show the participants` demographic characteristics by the researcher. In the second section, food habits were given and in the third section a questionnaire for measuring food information was applied. The questionnaire questions were arranged by screening the relevant literature, taking expert opinions and studying the questionnaires about food used in master and doctorate thesis before, thus the Cronbach`s alpha value was regarded to be "0.722" from the reliability analysis. When trainers and sportsmen` food information and food habits were compared in genders, it was seen that there were not any significant differences both females and males being trainers and females and males still doing sport (P>0.05). When food information and food habits were also compared in trainers and sportsmen, it was observed that there was a statistically significant difference between trainers and sportsmen (P<0.05). In conclusion, it was understood that sportsmen`s food information was better than trainers` food information as trainers` food habits were better than sportsmen`s food habits.